Pengaruh Penghargaan, Hukuman, dan Budaya Organisasi terhadap Kinerja Karyawan PT Mentari Mulia Berjangka - Safaria, Siti; Damayati, Elsa Kusumah (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This research aims to analyze the influence of rewards, punishment, and organizational culture on the performance of employees at PT. Mentari Mulia Berjangka. The method used in this research is a quantitative descriptice analysis method through a survey using questionnaire distribution as the media. The sample of respondents in this study consists of 98 respondents. The research data is processed using IBM SPSS Statistics. There are two types of variables in this study, namely independent variables and dependent variables. Independent variables include rewards, punishment, and organizational culture, while the dependent variable is employee performance. The research results indicate that rewards do not have a significant influence on employee performance. Punishment does not have a significant influence on employee performance. Organizational culture have a significant influence on employee performance. Keywords: organizational culture, punishment, performance, employee, reward